Problem dan Tantangan Lembaga Pendidikan Pondok Pesantren Salaf dan Modern - Iing, Iing (Bestari, 2021)
Pesantren as an educational institution develops with the times. The results of this are rising to two types of pesantren: salaf and modern. Until now, both types of pesantren still have problems and challenges. To be able to solve problems and challenges, the first thing that must be done is to identify the problems and challenges. This is a very important step for both pesantren so that both can exist. From these problems, there is motivation to study problems and challenges of modern and salaf pesantren. This study uses a descriptive method with a qualitative approach. The results of this study indicate that the problems of salaf pesantren are human resources, funds, facilities, communication access, kiai centric, a curriculum that is less relevant to the times, and institutional management, while the challenge is competition with formal schools, stigma as a place for radical Islamic cadres, and demands to adapt to government policies. The problems of modern pesantren are being too academically oriented, prioritizing formal education, and shifting values, while the challenges are preventing students from the negative influence of technology, adapting to the latest science and technology, and improving the quality of education.